The Regulation of Health Requirements for Police and Current Problems - Akçan, Ramazan; Yıldırım, Mahmut Şerif; Lale, Aykut; İsak, Abdurrahman; Cavlak, Mehmet; Odabaşı, Aysun Balseven; Tümer, Ali Rıza (The Bulletin of Legal Medicine, 2017)
Introduction: Forensic medicine specialists might prepare reports about health conditions of candidates for Police Organization or assessment of organization's staff based on The Regulation of Health Requirements for Police. The last update of regulation was performed in 2012; however, it is noteworthy that there still are definitions and articles contradicting current medical knowledge and make medical evaluation more challenging.Objective: In this study, we aimed to determine controversial articles based on evaluation of cases referred to our department and to discuss the issue in the context of related literature.Materials and Methods: Fifty-six patients who were admitted to Hacettepe University Faculty of Medicine, Department of Forensic Medicine between 01.03.2015 and 30.11.2015 for evaluation in respect of the Regulation of Health Requirements for Police were evaluated retrospectively and findings were discussed.Results: It was found that 47 of the 56 cases (83.9%) were male and 9 (16.1%) were female. Age of cases ranged between 18 and 33 years, with a mean age of 24.7 (SD=3.09) years. The controversial topics were mostly related to articles regarding visual acuity (refraction disorders)  and eye diseases (n=10, 17.9%) and Hepatitis B infections (n​​=5, 8.9%).Discussion and Conclusion: It is considered that above mentioned controversial issues might form a basis for updating the related regulation. In addition, it is important to revise the regulation periodically in order to maintain it up to date and avoid victimization.
Keywords: the regulation of health requirements for police; clinical forensic medicine; hepatitis b; refraction disorders